The Effect of TPR and Audio-Lingual Method in Teaching Vocabulary Viewed from Students’ IQ - Anita Dewi Ekawati (Journal of ELT Research: The Academic Journal of Studies in English Language Teaching and Learning, 2017)
This research aimed to investigate the effect of Total Physical Response (TPR) on elementary school students’ English vocabulary mastery with regards to their Intelligence Quotient (IQ). Whether or not there is an interaction between the teaching method and IQ in teaching vocabulary was also investigated in this study. The research was carried out at an elementary school in Central Java, Indonesia. The population was the fifth year students of two classes. Both the experimental and control groups consisted of 40 students. The data were analyzed using multifactor analysis of variance 2 x 2 (ANOVA). Then, it was analyzed using Tukey test. The study reveals that TPR was an effective method for teaching vocabulary in elementary school, and the effectiveness of the method was influenced by the level of students’ IQ. The results of the study may become a reference for EFL teachers to apply an effective method to teach English vocabulary to elementary school students. Moreover, EFL teachers need to take into account students’ IQ in implementing the teaching method.